Welcome to Westonci.ca, where your questions are met with accurate answers from a community of experts and enthusiasts. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
Substitute -x-2 for y in 3x+3y=6
3x+3y=6
3x+3(-x-2)=6
-6=6 (Simplify both sides of the equation)
-6+6=6+6 ( add six to both sides)
0=12
Answer: No Solutions
Hope this helped
3x+3y=6
3x+3(-x-2)=6
-6=6 (Simplify both sides of the equation)
-6+6=6+6 ( add six to both sides)
0=12
Answer: No Solutions
Hope this helped
Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Keep exploring Westonci.ca for more insightful answers to your questions. We're here to help.